Expression of the mouse corticotropin-releasing hormone gene in vivo and targeted inactivation in embryonic stem cells. - L J Muglia; N A Jenkins; D J Gilbert; N G Copeland; J A Majzoub (The Journal of Clinical Investigation, 1994)
Corticotropin-releasing hormone (CRH), one of the primary regulators of the hypothalamic-pituitary-adrenal (HPA) axis, exhibits abnormal regulation in pathologic states such as depression and anorexia nervosa. Analysis of the role of CRH in regulation of the HPA axis would be facilitated by the creation of animal models in which CRH gene structure and function could be manipulated. We have determined the DNA sequence of the mouse CRH gene. Using a highly sensitive reverse transcription-polymerase chain reaction method, we have found expression of CRH mRNA in adrenal, ovary, testis, gut, heart, anterior pituitary, lung, and spleen, in addition to cerebral cortex and hypothalamus. Within the spleen, CRH mRNA is localized specifically to T-lymphocytes. We mapped the chromosomal location of mouse CRH via interspecific mouse backcrosses to chromosome 3, which is not the site of any naturally occurring mutations consistent with CRH deficiency. Because of this, we inactivated a CRH allele in mouse embryonic stem (ES) cells by homologous recombination with a mutant mouse CRH gene lacking the entire coding region of preproCRH. Mice chimeric for each of two ES clones with an inactivated CRH allele are being used to generate animals with complete CRH deficiency. Images